Endogenous technology and tradable emission quotas - Rolf Golombek; Michael Hoel (University of Oslo, Department of Economics, 2006)
We study an international climate agreement that assigns emission quotas to each participating country. Unlike the simplest models in the literature, we assume that abatement costs are affected by R&D activities undertaken in all firms in all countries, i.e. abatement technologies are endogenous. In line with the Kyoto agreement we assume that the international climate agreement does not include R&D policies. We show that for a secondbest agreement, marginal costs of abatement should exceed the Pigovian level. Moreover, marginal costs of abatement differ across countries in the second-best quota agreement with heterogeneous countries. In other words, the second-best outcome cannot be achieved if emission quotas are tradable.
Keywords: H23; O30; Q20; Q25; Q28; 330; Climate policy; international climate agreements; emission quotas; technology spillovers; Klimaschutz; Spillover-Effekt; Theorie; Welt; Clean Development Mechanism; Emissionshandel